Optimalisasi Kecerdasan Spiritual Anak Melalui Yoga Asanas - Heny Perbowosari (Kamaya: Jurnal Ilmu Agama, 2018)
Spiritual intelligence is the intelligence that comes from the mind or soul of a person who always thinks positive so as to grow into a whole person. Developing children's spiritual intelligence needs to be done early on. The goal is for the child to be a person who has a sense of inner and soul towards himself and others. By developing spiritual intelligence in children, children will be more capable to recognize who they are, their strength and weakness, and be able to cover the weakness, as well as to sharpen and maximize the strength they have to be a successful person in the future. To optimize the spiritual intelligence of children, they can do yoga asanas. Yoga asanas movement for children is done in a relaxed and fun way so that they will not get bored quickly, such movements include learning the breath, imitating animal movements and relaxation. By doing yoga asanas, then they will be healthier, have a positive energy, and able to socialize as well.